Predictors of Burnout Syndrome Among Healthcare Workers in Hospitals - Janine Kieling Monteiro; Mary Sandra Carlotto (Interação em Psicologia, 2016)
This research aims at identifying sociodemographic and laboral predictors of burnout syndrome in 182 health workers in the hospital setting. It uses a questionnaire, Maslach Burnout Inventory, and a working context scale. In the analysis of the data a multiple regression analysis was employed. Interviewees' considering their profession as stressful was the most revealing variable with regards to the Emotional Exhaustion dimension and the low level of Professional Efficacy. As predictor variables to Cynicism the research points to negative working environments, stress upon dealing with male patients. The risk profile for burnout syndrome includes higher schooled professionals, old-timers and those who perceive their job, work scale, type and quantity of patients as stressing factors.